Exploring The Influence of Environmental Complexity on Entrepreneurial Decision Making: A Conceptual Review - Mercy Ejovwokeoghene Ogbari; George Uzoma K. Chima; Maxwell Ayodele Olokundun; Favour O. Olarewaju; Daniel.E. Ufua (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2022)
Practicing entrepreneurs make decisions in their business operations. These decisions are influenced by the environmental force and contextual issues that affect their operational process. This research paper focuses on exploring environmental complexities and their influence on entrepreneurial decision-making. The research applies a conceptual approach to unpack the effects of complexities, stakeholders’ perspectives and contextual issues on entrepreneurial decision process. A key suggestion is the adoption of meaningful engagement approach to addressing emerging complexities between entrepreneurship practice and environmental issues. While the research finds that interactive engagement can be slow in its process, it highlights the key advantages that could be useful to entrepreneurial practices.